ON THE METHODOLOGICAL FUNCTION OF REPEAT - Shofqorov A. M. (Bright Mind Publishing, 2025)
The article contains phonetic repetitions, their application in Mirtemir's poetry and a specific stylistic. The semantic-stylistic features of repetition of alliterations are represented.
Keywords: Repetition, phonetic repetition, alliteration, assonance, gemination, stylistic task.